A Multicenter Analysis Examining Patients Undergoing Conversion of Implant-based Breast Reconstruction to Abdominally based Free Tissue Transfer - Zhao, Ruya; Tran, Bao Ngoc N.; Doval, Andres F.; Broadwater, Gloria; Buretta, Kate J.; Orr, Jonah P.; Lee, Bernard T.; Hollenbeck, Scott T. (Journal of Reconstructive Microsurgery, 2018)
Background Breast implant placement is the most common method for postmastectomy reconstruction. For patients who develop complications associated with implant-based reconstruction, additional surgeries may be challenging. This study examined implant-based reconstruction failure in patients undergoing salvage with abdominal free tissue transfer.Methods We conducted an Institutional Review Board approved, multicenter retrospective study of patients with implant-based primary breast reconstruction followed by implant removal and subsequent abdominal free tissue transfer between 2006 and 2016. Patient demographics, treatment details, and complications were evaluated. Severity of implant failure was graded as either (1) not severe (delayed salvage reconstruction) or (2) severe (immediate salvage reconstruction).Results Between 2006 and 2016, 115 patients with 180 mastectomy defects underwent primary implant-based reconstruction with subsequent implant removal and abdominally based free tissue reconstruction. Of these, 68 were delayed and 47 were immediate salvage reconstruction. Factors leading to elective removal were capsular contracture, asymmetry, and implant malposition. Factors leading to obligatory removal were infection, delayed wound healing, and implant extrusion. Postmastectomy radiation was significantly associated with immediate salvage reconstruction (p < 0.001, odds ratio = 3.9) as were large volume implants (p = 0.06). Deep inferior epigastric perforator flaps comprised 78.3% of all abdominally based free tissue reconstructions, while muscle-sparing transverse rectus abdominus myocutaneous flaps comprised 18.3%. Overall flap failure rate was 2.6% (2.94% delayed and 2.13% immediate salvage reconstruction; p = 1.0).Conclusion Our findings suggest that abdominal free tissue transfer remains a safe and effective salvage modality for implant-based breast reconstruction failure. Patients with severe implant failure were more likely to have received radiation. Surgeons should remain cognizant of this during care of patients.
Keywords: breast reconstruction; abdominal free flap; salvage reconstruction